PENERAPAN PERMA NOMOR 4 TAHUN 2019 TENTANG GUGATAN SEDERHANA (SMALL CLAIM COURT) DALAM PENYELESAIAN PENUMPUKAN (KONGESTI) PERDATA PADA PENGADILAN DI SUMATERA BARAT - Ulfanora, Ulfanora; Amelia, Dian; Utama, Nanda (UNES Law Review, 2022)
The judicial process prioritizes legal certainty both in time and minimizes costs for the parties as Law Number 48 of 2009 in Article 2 and Article 4 paragraph (2) requires the existence of important principles in civil procedural law, namely Simple, Fast, Low Cost. Settlement of disputes at the first level with the a quo principle is certainly the hope of the whole community, especially those who want to resolve disputes through the courts, with the application of this principle, it is hoped that the settlement of cases, especially in the civil sector, will not be delayed and can be resolved in a short period of time, so that the costs incurred by the parties are not too high. However, the settlement of civil disputes through a simple trial under examination is regulated in a limited manner with a material claim value of a maximum of Rp. 500,000,000.00 (five hundred million rupiah) preceded by a dismissal process and the settlement period of this case is not more than 25 (twenty five) ) working days. The results of this study explain firstly the application of Perma Number 4 of 2019 procedures for resolving simple lawsuits at the District Court in West Sumatra can run effectively such as providing convenience for parties to access and register simple lawsuits both online and offline, educating Registrars and Judges about simple lawsuits so that can degrade errors (human error), as well as proven by a matrix of cases per year that are decided through a simple lawsuit. Second, the obstacle that often occurs in the process of resolving simple lawsuits is that judges often do not read the lawsuit comprehensively and immediately set a trial day so that when the trial takes place it is proven that the dispute cannot be resolved with a simple lawsuit (there are provisions in Articles 3 and 4 of this Perma). met) and ended up not being able to continue (NO).